2021
DOI: 10.1111/ced.14758
|View full text |Cite
|
Sign up to set email alerts
|

Infantile haemangioma presenting in combination with a cerebriform naevus sebaceous on the scalp

Abstract: Click https://wileyhealthlearning.com/#/online-courses/a54fac75-89f4-4bf5-80a4-19e31765a7a4 for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Although excision of IH presents the risk of bleeding due to the vascularity of the tumor, it may be necessary if the lesion is refractory to pharmacological treatment or causing life-threatening sequelae: recurrent bleeding, ulceration, congestive heart failure, or obstruction of a vital structure (airway, ear canal, and visual axis) 7,30 . Indications for surgical intervention of the scalp lesions in our review varied: 32% of patients exhibited critical anatomic disruption (4 ears, 2 eyes), 8,11,13,15 32% had ulceration or erosion, 9,11–14 16% with cardiac involvement, 8,10,15 11% with increased bleeding, 11,18 and 26% due to rapid growth or unresponsiveness to prior therapies 11,12,16,17 . Notably, excision was performed significantly earlier in patients with signs of cardiac involvement (<1 month) 8,10,15 …”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Although excision of IH presents the risk of bleeding due to the vascularity of the tumor, it may be necessary if the lesion is refractory to pharmacological treatment or causing life-threatening sequelae: recurrent bleeding, ulceration, congestive heart failure, or obstruction of a vital structure (airway, ear canal, and visual axis) 7,30 . Indications for surgical intervention of the scalp lesions in our review varied: 32% of patients exhibited critical anatomic disruption (4 ears, 2 eyes), 8,11,13,15 32% had ulceration or erosion, 9,11–14 16% with cardiac involvement, 8,10,15 11% with increased bleeding, 11,18 and 26% due to rapid growth or unresponsiveness to prior therapies 11,12,16,17 . Notably, excision was performed significantly earlier in patients with signs of cardiac involvement (<1 month) 8,10,15 …”
Section: Discussionmentioning
confidence: 92%
“…Review of the literature revealed 19 previously published case studies (from 1981 to 2022) of pediatric scalp hemangiomas undergoing excision (Supplemental Table 1, Supplemental Digital Content 1, http://links.lww.com/SCS/F594). [8][9][10][11][12][13][14][15][16][17][18] Of the patients whose sex was reported, the majority (78%) were female (F:M ratio of 3.5). Patient age at the time of excision ranged from 2 days old to 14 years old, with a median age of 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations